2008
DOI: 10.1111/j.1460-9568.2008.06093.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of transient receptor potential ankyrin 1 by hydrogen peroxide

Abstract: Hydrogen peroxide (H(2)O(2)), which is contained in industrial products, is also generated within cells. H(2)O(2) causes pain but it has not been elucidated how it activates sensory neurons in the pain pathway. Here we show that transient receptor potential ankyrin 1 (TRPA1), expressed by sensory neurons in the pain pathway, is a receptor for H(2)O(2). H(2)O(2) activated mouse TRPA1 to induce Ca(2+) influx and elicit non-selective cation currents. These effects of H(2)O(2) were mimicked by both reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
160
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 46 publications
9
160
1
Order By: Relevance
“…Covalent modification of TRPA1 by allyl-isothiocyanate or alkylating agents excites pain fibers, evoking acute pain and nocifensive behaviors. Hydrogen peroxide (H 2 O 2 ) and ␣,␤-unsaturated aldehydes acutely activate TRPA1 (12)(13)(14)(15). The reactive compound allicin from garlic and nitric oxide activate TRPA1 and TRPV1 via covalent modification (16)(17)(18)(19)(20)(21)(22), providing examples for oxidative stress-related pain or hyperalgesia.…”
mentioning
confidence: 99%
“…Covalent modification of TRPA1 by allyl-isothiocyanate or alkylating agents excites pain fibers, evoking acute pain and nocifensive behaviors. Hydrogen peroxide (H 2 O 2 ) and ␣,␤-unsaturated aldehydes acutely activate TRPA1 (12)(13)(14)(15). The reactive compound allicin from garlic and nitric oxide activate TRPA1 and TRPV1 via covalent modification (16)(17)(18)(19)(20)(21)(22), providing examples for oxidative stress-related pain or hyperalgesia.…”
mentioning
confidence: 99%
“…1C), we tested whether TRPA1 mediates the UVR photocurrent. TRPA1 is activated by numerous noxious compounds, pungent chemicals, and GPCRs (27)(28)(29)(30)(31), and was recently implicated in an extraocular UVR phototransduction system mediating light avoidance responses in Drosophila larvae (32).…”
mentioning
confidence: 99%
“…Similarly, whether or not TRPA1 functions as a sensor of noxious cold remains an unresolved question. Several studies demonstrated that noxious cold activates TRPA1 channels, both directly [118][119][120] and indirectly [121]. However, negative results were obtained in mouse TRPA1 channels heterologously expressed in human embryonic kidney cells [122], and neuronal activation by cold temperatures was found to be similar between wild-type and TRPA1 knock-out mice [123].…”
Section: Trpa1mentioning
confidence: 78%